A PARTICIPANT IN SOCIAL PROTEST. WHO IS HE AND WHY DOES HE PROTEST? AN ATTEMPT AT ANALYSIS - Lipold, Patrycja (European Scientific Journal, ESJ, 2014)
According to many studies and popular belief, it is a role of the global civil society, with its variety of actors, to act as an opposition to state which breaks all the rules. Taking state’s interests into consideration, lack of any counter-strategy towards growing power of citizens’ opposition can be disastrous. Citizens differ entirely from workers in the 19th century and this is what makes their power of opposition so dangerous for state. Today parliamentary democracy is supplemented by participatory democracy - participation of citizens. The problem lies in the fact that, while discouragement is typical for lower classes of society, the reaction of middle class is outrage and society expresses outrage but does not offer any alternatives. This division of the society into the discouraged and the outraged is very dangerous for democracy. Neither society nor modern democracy can exist without trust. Distrustful societies are a barometer for democracy. When everything goes well they form basis of new movements which consequently change into new ideas and projects. It is very difficult to use the potential of society but it is not impossible. Social protest is an inherent part of democracy but without an attempt to channel it, it is very dangerous.